Machine‐learning models for shoulder rehabilitation exercises classification using a wearable system - Sassi, Martina; Carnevale, Arianna; Mancuso, Matilde; Schena, Emiliano; Pecchia, Leandro; Longo, Umile Giuseppe (Knee surgery, sports traumatology, arthroscopy : official journal of the ESSKA, 2025)
Purpose The objective of this study is to train and test machine‐learning (ML) models to automatically classify shoulder rehabilitation exercises. Methods The cohort included both healthy and patients with rotator‐cuff (RC) tears. All participants performed six shoulder rehabilitation exercises, following guidelines developed by the American Society of Shoulder and Elbow Therapists. Each exercise was repeated six times, while wearing a wearable system equipped with three magneto‐inertial sensors. Six supervised machine‐learning models (k‐Nearest Neighbours, Support Vector Machine, Decision Tree, Random Forest (RF), Logistic Regression and Adaptive Boosting) were trained for the classification. The algorithms' ability to accurately classify exercise activities was evaluated using the nested cross‐validation method, with different combinations of outer and inner folds. Results A total of 19 healthy subjects and 17 patients with complete RC tears were enroled in the study. The highest classification performances were achieved by the RF classifier, with an accuracy of 89.91% and an F1‐score of 89.89%. Conclusion The results of this study highlight the feasibility and effectiveness of using wearable sensors and ML algorithms to accurately classify shoulder rehabilitation exercises. These findings suggest promising prospects for implementing the proposed wearable system in remote home‐based monitoring scenarios. The ease of setup and modularity of the system reduce user burden enabling patient‐driven sensor positioning. Level of Evidence Level III.